Big questions from little people--- and simple answers from great minds - Harris, Gemma Elwin (Ecco, 2012)
Many of the questions children ask in the course of growing up can stump even the best educated adult: Why can't l tickle myself? Are we all related? Who named all the cities? Do aliens exist? What makes me me? Is it okay to eat a worm? Who invented chocolate? If the universe started from nothing, how did it become something? How do you fall in love? Who is God? How do chefs get ideas for recipes? Why are some people mean? This charming and informative collection has been compiled from schoolchildren's actual questions, which are answered by the world's greatest experts, including Mary Roach, Richard Dawkins, Philip Pullman, Bear Grylls, David Eagleman, Philippa Gregory, Noam Chomsky and Mario Batali. --Publisher description.